Construct validity and reliability of a checklist for volleyball serve analysis - Cicero Luciano Alves Costa; Paulo Felipe Ribeiro Bandeira; Cintia de Oliveira Matos; Madson Pereira Cruz; Herbert Ugrinowitsch (Universidade Federal de Santa Catarina, 2018)
This study aims to investigate the construct validity and reliability of the checklist for qualitative analysis of the overhand serve in Volleyball. Fifty-five male subjects aged 13-17 years participated in the study. The overhand serve was analyzed using the checklist proposed by Meira Junior (2003), which analyzes the pattern of serve movement in four phases: (I) initial position, (II) ball lifting, (III) ball attacking, and (IV) finalization. Construct validity was analyzed using confirmatory factorial analysis and reliability through the Cronbach's alpha coefficient. The construct validity was supported by confirmatory factor analysis with the RMSEA results (0.037 [confidence interval 90% = 0.020-0.040]), CFI (0.970) and TLI (0.950) indicating good fit of the model. In relation to reliability, Cronbach's alpha coefficient was 0.661, being this value considered acceptable. Among the items on the checklist, ball lifting and attacking showed higher factor loadings, 0.69 and 0.99, respectively. In summary, the checklist for the qualitative analysis of the overhand serve of Meira Junior (2003) can be considered a valid and reliable instrument for use in research in the field of Sports Sciences.